Calle Real an examination of Iloilo City's core downtowm district and methods for its reinvention as the City's identifying mode - Coo, Antoine Geoffrey V.; Mata, Rene Luis (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
In the developing world, cities remain primary economic & cultural centers, thus, the development and sustainability of city centers continue to be important issues for urban planners and policy makers. As economies develop and populations increase across the globe, it is viewed that the vitality of city centers are reflections of a city's sustainability and viability, and urban planning plays a significant role in ensuring that environments remain vital and support the needs of the population. In countries such as the Philippines, the trend has been for cities to expand, as manifested by the expansion of, for instance, the city of Manila, into Metro Manila, and further into the Greater Manila Area. Reflecting this same development, other urban centers in the country's regions are seen to potentially develop in the same manner. In Region VI of Western Visayas, a region in the central part of the country comprising the provinces of Aklan, Antique, Capiz, Guimaras, and Iloilo and the cities of Iloilo City (Iloilo), Roxas City (Capiz) and Passi City (Iloilo), Metro Iloilo can be considered the epicenter of educational, cultural and economic activity. Paradoxically, with these expansions, economic and cultural activity becomes less concentrated in city centers, resulting in a neglect or ignorance for maintaining built heritage within traditional city centers which may weaken a place's cultural identity. A place with a weak cultural identity may find it difficult to harness both the community and the physical environment and, thus, fail to provide the necessary structural support for a vibrant and dynamic center.Neighborhoods with an intact physical heritage serve important functions to communities, as built heritage are physical manifestations of a community's values and ideals. As an identifying node, well-maintained built heritage sustain cultural activity and typically become sources of economic activity as well. Places with dynamic cultural activity reflect an engaged citizenry more willing to ensure that good policy in all aspects of life are adapted and implemented for the greater population; an engaged citizenry tend to create innovative economic activity rooted in the community's cultural values and mores. And so, it has been established that urban heritage conservation is not done to stop the workings of a neighborhood, turning them into museums but, rather, done to improve and revitalize the place as a center for community or communal activity, while at the same time safeguarding built heritage's historical value.In the Western Visayas Region (Region VI), Iloilo City has been identified not only as a regional urban center, but a city steeped in culture and history. Until the 13th century, islanders lived in an organized government run under the rules of the Code of Kalantiaw. In 1566, the first Spanish conquistadores led by Miguel Lopez de Legazpi settled in Ogtong (the present-day Oton), located at the south of the Jaro River, the city was for a long time under the Spanish regime, remnants of which are markedly evident in the architecture of its buildings and famous churches.
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: FI